Comparison of Transcriptome Profiles of the Fungus Botrytis cinerea and Insect Pest Bradysia odoriphaga in Response to Benzothiazole - Cui, Kaidi; Zhao, Yunhe; He, Leiming; Ding, Jinfeng; Li, Beixing; Mu, Wei; Liu, Feng (Frontiers in Microbiology, 2020)
Benzothiazole has a strong inhibitory effect on the growth and development of a wide spectrum of fungi and insects, such as Botrytis cinerea and Bradysia odoriphaga, that cause serious losses in agriculture. To investigate the underlying antifungal and insecticidal mechanisms of benzothiazole, RNA-seq analysis was performed for B. cinerea after benzothiazole treatment for 12, 24 and 48 h and B. odoriphaga after benzothiazole treatment for 6 and 24 h. In B. cinerea, the pectin degradation process was inhibited, suggesting a low utilization of carbohydrate sources. As the treatment time was extended, the cell walls of B. cinerea thickened, and increases in melanin synthesis and ion transport were observed. In B. odoriphaga, signaling pathways including MAPK, insulin, adipocytokine, FoxO and PPAR were activated at 6 h, and phosphoenolpyruvate carboxykinase (PEPCK) was the core gene in the signal transduction pathways responding to benzothiazole; digestive system and melanogenesis genes were obviously altered at 24 h. In addition, we identified several insecticidal target genes, such as trypsin, aminopeptidase N and tyrosinase. Benzothiazole significantly affected nutrient metabolism, especially carbohydrate metabolism, in both species, and the pentose and glucuronate interconversions pathway was shared by both species, although the individual genes were different in each species. Overall, our results suggested that benzothiazole was a melanogenesis disrupter for the insect but an activator for the fungus. Our findings are helpful for deeply exploring the genes targeted by benzothiazole and for developing new pesticide compounds with unique mechanisms of action.